The competitive advantage in the global labour market - Kajanová, Jana (Business, Management and Economics Engineering, 2011)
The main subject of this paper is to present and submit the basis of both internal and external factors determining the competitive advantages in the global labour market and to assess the possibilities and changes occurring in the current labour market due to the present-day requirements of this sphere. Today, it is necessary to take into account a certain advantage in comparison to other applicants in the market place. It follows that the matter in question is the creation of the competitive advantage, which will strengthen the position of an applicant, point out to the causes of his preference and will provide interesting conditions.